ASSESSMENT OF LIFE SATISFACTION OF RUSSIAN POPULATION IN 1993–2013 - Margarita Perova; Evgeniy Perov (European Scientific Journal, ESJ, 2015)
The degree of population satisfaction with life characterizes the state of society and does not remain constant. It is characterized by the coefficient of life satisfaction that is based on the data of sociological polls. The dynamics of the coefficient shows that the assessment of life satisfaction of the Russian population was negative up to 2006, and in subsequent years it has become positive. The degree of life satisfaction is influenced by objective factors (income and expenditure of population, GDP per capita, unemployment, etc.), as well as by subjective factors (gender, age, marital status, social status, mood state, etc.).